Surgical treatment of spinal tuberculosis: an updated review - Jinjing Gan; Chuanzhi Zhang; Dagang Tang; Xing Du (European Journal of Medical Research)
Abstract Tuberculosis (TB) is a worldwide disease which seriously affects the global public health. Spinal TB is the most common extra-pulmonary TB and may cause vertebral bone destruction, collapse, kyphosis and even paralysis. Anti-TB chemotherapy is considered the cornerstone treatment of spinal TB and surgery is often required for patients with severe kyphosis, impaired neurological function or spinal instability. Debridement of TB lesions, bone grafting and internal fixation are the key procedures of spinal TB surgery. However, the selection of surgical approach, the extent of TB lesion debridement, the choice of bone graft materials, and the method and extent of internal fixation are all remain controversy. The aim of this updated review is to evaluate current literature for advances in management of spinal TB, with particular focus on surgical techniques.